Prevalence & Identification of Risk Factors of Fall in Elderly Population (VIMS Health Science Journal, 2015)
Background: the geriatric populations are having common problems related to their health in which common is fall. A fall is when a sudden, unintended loss of balance leaves the individual in contact with the floor or another surface such as a step or chair. This happens because of fear of fall in among these geriatric peoples. Objectives: to find out the prevalence and identification of risk factors of fall in elderly population. Method: this was an observational study in which total 40 participants were selected, according to inclusion and exclusion criteria by purposive sampling and data was collected. Result: out of 40 participants the mean age was 69 years and the fear of fall in these participants were moderate according to MFES (modified Fall Efficacy Scale) and there were more falls seen in females as compared to males. Conclusion: with the help of this research we concluded that there were a high prevalence of fear of falling among elderly population
Keywords: Prevalence of fall in elderly; Modified efficacy scale